Pengaruh Chatbot AI terhadap Beban Kerja Layanan Pelanggan Grab di Kota Medan - Sandi Nugraha; Muhammad Irwan Padli Nasution (CV. ITTC INDONESIA, 2024)
This study aims to analyze the influence of AI-based chatbots on reducing customer service workload at Grab, specifically within the context of transportation and delivery services in Medan City. In an increasingly digital era, companies must adapt to new technologies to enhance operational efficiency and customer satisfaction. The research method employed is quantitative with a case study approach. Data were collected through surveys of 100 customer service agents and 200 Grab users who have interacted with the chatbot. The results indicate that 75% of agents experienced a reduction in workload, with an average response time improvement of 30%. On the user side, 65% expressed satisfaction with the chatbot service, although 20% reported frustration due to the chatbot's limitations in handling complex queries. Historical data also revealed a 40% increase in interactions redirected to the chatbot and a 25% decrease in tickets escalated to agents. This study concludes that the implementation of AI-based chatbots has a positive impact on customer service efficiency, but it also highlights the importance of further development to enhance user experience. Recommendations for future research include exploring the development of more advanced chatbot features and training for agents to maximize the synergy between technology and human interaction.